2023
DOI: 10.3390/antiox12020260
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling Quince Peel into Bioactive Ingredients and Fiber Concentrates through Multicomponent Extraction Processes

Abstract: This study aimed to promote the total upcycling of quince (Cydonia oblonga Mill.) peel into bioactive extracts (BEs) and fiber concentrates (FCs). The multicomponent extraction processes were optimized using response surface methodology (RSM) coupled with a 20-run experimental design, where the effects of time (1–120 min), temperature (25–95 °C), and EtOH percentage (0–100%) were combined. In addition to the extraction yields, BEs were analyzed for phenolic compounds, organic acids, and other water-soluble con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…Non-cellulose polysaccharides refer to the carbohydrates in a sample other than cellulose, including digestible sugars, starches, and other soluble and insoluble carbohydrates. Our results showed that the levels of TCC were slightly lower than the values reported in [7] from quince peels, which were determined using an enzymatic-gravimetric method. The highest levels of TCC and NCP were observed in the S_QPE-substrate of the quince pomace after treatment with ethanol.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…Non-cellulose polysaccharides refer to the carbohydrates in a sample other than cellulose, including digestible sugars, starches, and other soluble and insoluble carbohydrates. Our results showed that the levels of TCC were slightly lower than the values reported in [7] from quince peels, which were determined using an enzymatic-gravimetric method. The highest levels of TCC and NCP were observed in the S_QPE-substrate of the quince pomace after treatment with ethanol.…”
Section: Resultscontrasting
confidence: 83%
“…Previous studies have investigated the properties of the fiber-rich products from quince (Cydonia oblonga) wastes after aqueous or ethanol extraction, but they did not evaluate the properties and possible applications of the resulting extracts [6,7]. A recent study analyzed the acetone extraction of C. oblonga fruits, but it did not characterize the resulting substrate [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the antimicrobial effect of the plant, gram negative bacteria were more sensitive to the extracts, while the extracts obtained from C. oblonga flour showed growth inhibitory effect on Aspergillus niger (A. niger) [41]. To promote the full reuse of this plant, biologically active extracts and fiber concentrates of the plant were extracted and found to exhibit in vitro antioxidant activity as well as antimicrobial activity against food borne fungi and bacteria, suggesting that various extracts of the plant could be pioneers in the use of natural preservatives in foods [42]. Dye was obtained from the extract of C. oblonga plant in order to work on recovery to nature and dyeing process was carried out with various chemicals as a coloring agent on wool.…”
Section: Discussionmentioning
confidence: 99%